Emerging Role of Proteases in the Pathogenesis of Chronic Rhinosinusitis with Nasal Polyps - Wu, Dawei; Wei, Yongxiang; Bleier, Benjamin S. (Frontiers in Cellular and Infection Microbiology, 2018)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous upper airway disease with multiple etiologies. Clinically, CRSwNP can be classified into either eosinophilic or non-eosinophilic subtypes. The eosinophilic phenotype of CRSwNP is widely thought to be highly associated with recurrence of nasal polyps or surgical failure. Epithelial cells have a crucial role in the development of Th2-biased airway diseases. Recent studies have shown that a wide range of external stimuli such as allergens and microorganisms can elicit the release of epithelial-derived Th2-driving cytokines and chemokines. Protease activity is a feature common to these multiple environmental insults and there is growing evidence for the concept that an imbalance of proteases and protease inhibitors in the epithelial barrier leads to both the initiation and maintenance of chronic eosinophilic airway inflammation. In this review, we analyze recent work on the role of proteases in the development of the sinonasal mucosal type 2 immune response with an emphasis on the molecular pathways promoting adaptive Th2 cell immunity.